2003
DOI: 10.1046/j.1460-9568.2003.02485.x
|View full text |Cite
|
Sign up to set email alerts
|

The eye of the african mole‐ratCryptomys anselli: to see or not to see?

Abstract: In an attempt to clarify its possible physiological role, we studied the eye of the Zambian mole rat Cryptomys anselli by light, electron and confocal microscopy using conventional staining as well as immunolabelling with rod and cone cell markers. The small eyes of Cryptomys are located superficially and display all features typical of sighted animals: iris, pupil and well-developed lens, separating the anterior chamber and the vitreous. The retina shows a well stratified organization and the folds described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 62 publications
2
41
1
Order By: Relevance
“…Contrary to the putative connection of magnetite-based receptors with the ophthalmic nerve, Cernuda-Cernuda et al (Cernuda-Cernuda et al, 2003) reported findings of retinal crystalloid bodies in the inner photoreceptor segment of the Ansell's mole-rat. The authors interpreted these structures as potential magnetite grains, and suggested the retinal photoreceptors as the magnetite-based structure.…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to the putative connection of magnetite-based receptors with the ophthalmic nerve, Cernuda-Cernuda et al (Cernuda-Cernuda et al, 2003) reported findings of retinal crystalloid bodies in the inner photoreceptor segment of the Ansell's mole-rat. The authors interpreted these structures as potential magnetite grains, and suggested the retinal photoreceptors as the magnetite-based structure.…”
Section: Discussionmentioning
confidence: 91%
“…It should be noted that Ansel"s and Damaraland mole rats were previously considered to be members of the genus Cryptomys. All three species of mole rat have a reduced visual system, live a subterranean lifestyle and have unusual patterns of circadian rhythmicity (Lovegrove and Papenfus, 1995;Lovegrove and Muir, 1996;Oelschlager et al, 2000;Cernuda-Cernuda et al, 2003;Negroni et al, 2003;Oosthuizen et al, 2003;Gutjahr et al, 2004;Nemec et al, 2004;Nemec et al, 2008). Brains from circadian distinct rhythmic and arrhythmic individuals of each species were examined.…”
Section: Introductionmentioning
confidence: 99%
“…The model species to support such claims is the muroid blind mole-rat Spalax ehrenbergi, which has atrophied subcutaneous eyes and retinal deficits (Sanyal et al, 1990;Cooper et al, 1993;Cernuda-Cernuda et al, 2002;David-Grey et al, 2002). On the other hand, recent studies on subterranean African mole-rats (bathyergid rodents) have reported small but well-developed eyes with photoreceptor properties that suggest visual capabilities at higher light levels (Cernuda-Cernuda et al, 2003;Peichl et al, 2004). These findings call for a more differentiating view of visual regression in subterranean species.…”
mentioning
confidence: 99%